Musical neglect training for chronic persistent left hemispatial neglect with right hemiplegia post-stroke: a case report - Yuka Kasuya-Ueba; Yuka Kasuya-Ueba; Koji Maeda (Frontiers in Rehabilitation Sciences)
A 69-year-old right-handed man, who initially suffered a stroke 8 years ago and experienced two recurrences since then, presented with right hemiplegia and left hemispatial neglect as a post-stroke syndrome in the chronic phase. This report demonstrates the use of active musical instrument playing with Musical Neglect Training (MNT®) to improve severe left-side neglect and activities of daily living (ADLs). In addition to physical and occupational therapy, individual MNT® was incorporated into the patient's rehabilitation plan to improve his hemispatial neglect. At the initiation of the intervention, the number of uncrossed lines on the line cancellation test was 33 out of 40, and his Mini-Mental State Examination score was 17. Regarding ADLs, egocentric neglect was observed, especially during eating and wheelchair operations. Over the course of 18 months of weekly individual MNT®, a remarkable improvement was observed in the line cancellation test score (number of uncrossed lines = 4) and in ADLs. Follow-up tests showed that the effects of the intervention lasted at least 6 months. This is the first reported case demonstrating long-term effects observed at 6 months after an 18-month intervention period employing MNT® in a patient with severe chronic persistent hemispatial neglect. While rigorous studies are needed, our findings encourage further investigation of the benefits of MNT® interventions in post-stroke rehabilitation. In summary, long-term intervention involving active musical instrument playing, using auditory stimulus cues, significantly improved the severe symptoms of left hemispatial neglect in a patient with right hemiplegia, even during the chronic phase of recovery.